Maturation of Plastid c-type Cytochromes - Gabilly, Stéphane T.; Hamel, Patrice P. (Frontiers in Plant Science, 2017)
Cytochromes c are hemoproteins, with the prosthetic group covalently linked to the apoprotein, which function as electron carriers. A class of cytochromes c is defined by a CXXCH heme-binding motif where the cysteines form thioether bonds with the vinyl groups of heme. Plastids are known to contain up to three cytochromes c. The membrane-bound cytochrome f and soluble cytochrome c6 operate in photosynthesis while the activity of soluble cytochrome c6A remains unknown. Conversion of apo- to holocytochrome c occurs in the thylakoid lumen and requires the independent transport of apocytochrome and heme across the thylakoid membrane followed by the stereospecific attachment of ferroheme via thioether linkages. Attachment of heme to apoforms of plastid cytochromes c is dependent upon the products of the CCS (for cytochrome c synthesis) genes, first uncovered via genetic analysis of photosynthetic deficient mutants in the green alga Chlamydomonas reinhardtii. The CCS pathway also occurs in cyanobacteria and several bacteria. CcsA and CCS1, the signature components of the CCS pathway are polytopic membrane proteins proposed to operate in the delivery of heme from the stroma to the lumen, and also in the catalysis of the heme ligation reaction. CCDA, CCS4, and CCS5 are components of trans-thylakoid pathways that deliver reducing equivalents in order to maintain the heme-binding cysteines in a reduced form prior to thioether bond formation. While only four CCS components are needed in bacteria, at least eight components are required for plastid cytochrome c assembly, suggesting the biochemistry of thioether formation is more nuanced in the plastid system.